Magic and warfare: appearance and reality in contemporary African conflict and beyond - Wlodarczyk, Nathalie (Palgrave Macmillan, 2009)
"Magic" in contemporary Africa -- Spirits in battle -- Thinking about practice in warfare -- Notes on the case study -- The Sierra Leone Civil War and civil defence -- Spiritual context as habitus and capital -- Creating magic soldiers : Kamajor mobilisation and initiation -- The Kamajors in battle : magic, tactics, and success -- Local practice and the wider world of warfare